Pemanfaatan Media Sosial Youtube MetroTV Sebagai Media Kampanye Anies Baswedan Menjadi Calon Presiden 2024 - Solihin, Olih; Setiawan, Muhammad Rifki; Hariyati, Farida Afif; Rahmawati, Yulia (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2024)
The current elections are heavily influenced by the advancements in information technology, one of which is the emergence of the video-sharing application YouTube. The research aims to analyze the utilization of MetroTV's social media platform YouTube as a campaign medium for Anies Baswedan, focusing on the roles of media, neutrality, openness, and ethics. This qualitative research employs content analysis methodology. The findings are as follows: Role: Metro TV utilizes the YouTube platform to enhance political content, particularly related to Anies Baswedan, strengthening the role of social media in shaping public opinion; Neutrality: Concerns arise regarding Metro TV's neutrality in presenting political content, especially with the increase in Anies Baswedan-related content, raising questions about fair access in delivering political messages; Openness: Metro TV demonstrates openness by uploading